The Influence of Using Enterprise Resource Planning (ERP) Technology and Knowledge Management on the Quality of Accounting Information Systems - Bakri Bakri; Sri Mulyani (International Journal of Supply Chain Management, 2019)
Abstract: This study aims to determine the effect of using enterprise resource planning (ERP) technology and knowledge management on the quality of accounting information systems. The study was conducted on 30 state-owned enterprises in Gorontalo province where the respondents were managers, and financial heads / supervisors, using survey methods. Data testing uses Structural Equation Modeling (SEM) with Part Least Square (PLS) analysis approach.The results of the study prove that the use of enterprise resource planning (ERP) technology affects the quality of accounting information systems, and knowledge management influences the quality of accounting information systems. Enterprise Resource Planning technology has been integrated in all lines in state-owned enterprises, as well as knowledge management has been implemented well in all organizational lines.Keywords: Enterprise resource planning technology, Knowledge management, quality of accounting information systems.